(untitled) (Anwer Khan Modern Medical College Journal, 2015)
Background: The physiological role of adiponectin is not yet fully clear, but it is now generally accepted that it has a protective role against the development of lifestyle disorders, related to insulin resistance and atherosclerosis. Insulin resistance is one of the basic defects of type 2 diabetes (T2DM) and adiponectin is inversely associated with T2DM. As serum adiponectin level has not yet been investigated in Bangladeshi T2DM subjects,so that the present study has been under taken to find out the association of T2DM with serum adiponectin level in Bangladeshi population. Methodology: In this observational case control study, sixty six (66) T2DM subjects, seventy four (74) healthy control subjects were included. Diabetes was diagnosed and classified as per WHO criteria. Serum Adiponectin was measured by Enzyme Linked Immunosorbent Assay (ELISA) method. Serum glucose was measured by glucose-oxidase method; serum insulin was measured by chemiluminescence-based ELISA technique. The insulin secretory capacity (HOMA%B), insulin sensitivity (HOMA%S) & insulin resistance (HOMA IR) were assayed by homeostasis model assessment method. Results: The study subjects were BMI matched. BMI of the Control subjects and T2DM subjects (Mean±SD) were 25.02±3.55 and 25.85±3.62. Age (year) of the Control subjects and T2DM subjects (Mean±SD) were 42.46±9.24 and 48.49±8.09. Median (range) fasting serum insulin in the control and T2DM was 14.68 (1.86-45.92) and 18.09 (4.10-42.78) respectively which was not statistically significant (p=0.214). Median (range) HOMA%B values in the control and T2DM subjects was 160.10(33.40-493.40) and 100.45(17.70-349.30). Median HOMA%B in the T2DM group was significantly lower compared to the control (p=0.0001). Median (range) HOMA%S values in the control and T2DM subjects was 44.20(9.80- 339.40) and 32.80(14.30-154.70) respectively. Median HOMA%S in the T2DM group was significantly lower compared to the control (p=0.036). Median (range) serum adiponectin (?g/ml) of the control and T2DM subjects was 8.70 (0.76-15.96) and 6.19 (1.13-22.37). Serum adiponectin was significantly lower in T2DM compared to the control (p=0.0001). Conclusions: From this study it may be concluded that, T2DM subjects have both insulin secretory defects and insulin resistance and associated with lower serum adiponectin level in Bangladeshi population. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 10-13